2007
DOI: 10.1002/adsc.200700161
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Metathesis of Amine‐Containing Systems: Beyond the Current Consensus

Abstract: Olefin metathesis is one of the most powerful synthetic tool to access amine-containing heterocycles and alkaloids. A major drawback associated with the use of amines concerns their ability to coordinate to metal-alkylidene complexes and to interfere unproductively with catalytic activity. Based on literature precedents, it has been established as a "dogma" that efficient metathesis reactions are suppressed in the presence of basic amines and that such substrates must invariably be deactivated by conversion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(85 citation statements)
references
References 128 publications
1
83
0
1
Order By: Relevance
“…Such chelation effects are not unprecedented in olefin metathesis. Similar effects have also been observed during olefin metathesis of amine-containing systems (Compain, 2007). Based on these studies, we believe the low observed conversion may be a result of coordination between the Ru atom of the HG-2 catalyst and the carbonyl or amine group of the amide, as shown in Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Such chelation effects are not unprecedented in olefin metathesis. Similar effects have also been observed during olefin metathesis of amine-containing systems (Compain, 2007). Based on these studies, we believe the low observed conversion may be a result of coordination between the Ru atom of the HG-2 catalyst and the carbonyl or amine group of the amide, as shown in Fig.…”
Section: Resultssupporting
confidence: 52%
“…3. While the problematic amine group can be masked by protecting groups or by in situ formation of ammonium salts with the help of acid additives (Compain, 2007;Formentin et al, 2005), this is not an option for amides, which are not sufficiently basic to readily form salts and for which protection/deprotection techniques are limited. However, based on the proposed chelation mechanism, it is reasonable to speculate that any factors that can lower the effective electron density on the amide would weaken the potential for chelation and thus increase the metathesis activity.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of an amide group should allow an easy outcome of RCM. 16 In fact, amide (R)-10, treated with a Grubbs catalyst of 2 nd generation 11 in DCM at reflux, furnished hexahydroquinolizinone (R)-12 in quantitative yield. 17 The reaction proceeds through an initial coordination of the Ru-species to the allylic carbon-carbon double bond; the olefin metathesis of electron-poor double bonds was less favoured compared to neutral olefins because of the relative instability of electron-deficient metal carbene bonds.…”
Section: Synthetic Sequence Based On the Rcm Reactionmentioning
confidence: 99%
“…These structures still represent rare examples of 16 cis-dichloro ruthenium complexes for metathesis in which a monodentate 17 phosphorus ligand is involved [47, 48], and the first examples of 18 indenylidene-type complexes displaying such configuration. The cis-19 dichloro geometry has been found more common in Hoveyda-type 20 complexes featuring bidentate ligands [49][50][51][52][53][54][55][56][57][58]. 21 with a large cone angle such as P(OiPr) 3 and P(OPh) 3 , required longer 6 reaction times than the smaller P(OMe) 3 and P(OEt) 3 (Table 1).…”
Section: Synthesis Of Ruthenium Nhc Phosphites Complexes 18mentioning
confidence: 99%